Advancing Parent and Newborn Health Outcomes Through Community-Based Collaboration: A Somerville-Tufts University Partnership - Siwaar Abouhala; Nina Ashford; Ameya Menta; Stephanie Saintilien; Elizabeth Bolarinwa; Lily Snape; Ana Nieto; Fernanda Villar; Ndidiamaka Amutah-Onukagha (Journal of Participatory Research Methods)
This manuscript is based on Project INSPIRE: Improving New Somerville Parent & Infant Resiliency & Engagement, a healthcare and early childcare sector collaboration between: 1) the Center for Black Maternal Health and Reproductive Justice (CBMHRJ) at Tufts University School of Medicine in Boston, Massachusetts; 2) MARCH: Maternal Advocacy and Research for Community Health at Tufts University in Medford, Massachusetts; and 3) SomerBaby, an early childhood home-visiting and parental support program through Somerville Public Schools in Somerville, Massachusetts. To address Somerville immigrant parental health gaps in the literature, we convened a Parent Advisory Board (PAB), co-created a novel health needs assessment survey in English, Spanish, and Portuguese, and distributed this survey both through home visits by SomerBaby interpreters as well as online for all Somerville parents of children three years old or younger. In this manuscript, we focus on topics related to the overall methodology of this project, including study conceptualization, lessons learned in community-engaged parental health research, and recommendations for academic-community research partnerships in pursuit of Black and Brown maternal health equity.